Addressing the hypothyroidism impasse - seeking a consensus for the treatment of dissatisfied hypothyroid patients - Welborn, Tim (Frontiers in Endocrinology, 2025)
Physicians demonstrate differing attitudes about the management of hypothyroid patients on optimal replacement with thyroxine (T4) who have persisting symptoms. The use of liothyronine (T3) as combination therapy (T4+T3) has been promoted, and some patients demonstrate a compelling benefit. They can be identified by delayed relaxation of tendon reflexes, that is, a positive Woltman’s sign. This is specific for T3 responders. A generation of Endocrinologists has neglected this useful clinical sign. Patients with autoimmune symptoms and elevated anti-thyroid peroxidase (anti-TPO) antibodies show improvement after total thyroidectomy, but with the risk of significant postoperative complications. This discrete subgroup tends to be disregarded by authorities in the literature. There is a compelling need for further research on the nonsurgical treatment of this subgroup. Many dissatisfied patients have psychosomatic symptoms because of the burden of having a chronic disease, the need to take regular medication, and other psychosocial concerns. They have medically not yet explained symptoms (MNYES) and require support, counselling, and sometimes cognitive behaviour therapy. True thyroxine allergy and/or sensitivity does occur but is extremely rare. These four subgroups could be designated as – (1) T3-hypothyroidism; (2) Anti-TPO-toxic hypothyroidism; (3) Hypothyroidism-in-denial; and (4) Thyroxine- sensitivity. Recognition of these individual categories is necessary to achieve agreement among physicians and to promote further targeted research.